Modular Approach to the Synthesis of Polydentate NHC-Ligand Precursors (Benzimidazolium Salts) Containing Axial Chiral 1,1′-Binaphthyl via Pd-Catalyzed N-Arylation of 1,2-Diaminobenzene - Zhu, Shifa; Wang, Chao; Zhao, Songxian; Xiao, Yelin; Hu, Lang; Huang, Zhipeng (Synthesis, 2014)
A convenient and efficient modular approach to the synthesis of polydentate NHC ligand precursors (benzimidazolium salts) containing axial chiral 1,1′-binaphthyl from 1,2-diaminobenzene and BINOL has been developed. The benzimidazolium salts could be regarded as the potential bidentate, tridentate, and tetradentate NHC ligand precursors.
Keywords: NHC; benzimidazolium salt; N-arylation; Pd-catalyzed